'Home is home': journeying and living from Ethiopia to Johannesburg. Issue 1 (2nd January 2020) - Halligey, Alex
ABSTRACT: An Ethiopian immigrant in Johannesburg, Mewish, describes the housing she has lived in since leaving Ethiopia in 2002. The interview is framed as a testimony to the kinds of daily actions towards finding shelter and making a home that might be considered forms of micro activism, daily actions of resistance and change making in precarious housing circumstances.